Interrupting practice traditions: using readers' theatre to show the impact of a nationally mandated assessment task on initial teacher educators' work. Issue 4 (2nd October 2022) - Keamy, Ron Kim; Selkrig, Mark
ABSTRACT: The mandated introduction of a teaching performance assessment (TPA) into initial teacher education programs in Australia is one of the numerous and continual reforms that have impacted those who work in the field. The Assessment for Graduate Teaching (AfGT) is an approved TPA developed by a national consortium of higher education institutions to determine the 'classroom readiness' of graduating teachers. Surveys and focus group discussions were conducted with stakeholder groups to explore their experiences of trialling and implementing the AfGT. Initial teacher educators identified several aspects related to implementation that had impacted the ways they work, which included experiencing an increased workload. A semi-fictionalised narrative in the form of a readers' theatre script was developed to weave initial teacher educators' accounts together in an anonymised yet believable fashion for presentation at a research conference. The resultant script provides illustrations of the changing and complex nature of teacher educators' work because of the introduction of the AfGT, and when considered through the theory of practice architectures, it becomes evident that practice traditions are also interrupted.